2021
DOI: 10.1111/dmcn.14870
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life measures in pediatric multiple sclerosis: a systematic review and meta‐analysis

Abstract: Aim To identify generic measures used to measure quality of life (QoL) in pediatric multiple sclerosis research, estimate an overall score of children and adolescents with pediatric multiple sclerosis, and compare the scores to scores of typically developing children and adolescents. Method A systematic search was conducted on four databases. All studies were included if: the sample was children with pediatric demyelinating disorders; self‐reported QoL/health‐related quality of life (HRQoL) measures or results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The HRQoL evaluated in our study showed the mean score of 66.5±16.2. In the validation and reliability study of Turkish PedsQL for adolescents aged 13 to 18 years, the mean PedsQL score of patients with chronic diseases was 74.82 and a recent systematic review and meta-analysis in POMS patients using PedsQL, reported mean HRQoL scores as 67.3-82.4 (15). The mean PedsQL score of our POMS patients was in the lower range of those reported in this meta-analysis.…”
Section: Discussionmentioning
confidence: 42%
“…The HRQoL evaluated in our study showed the mean score of 66.5±16.2. In the validation and reliability study of Turkish PedsQL for adolescents aged 13 to 18 years, the mean PedsQL score of patients with chronic diseases was 74.82 and a recent systematic review and meta-analysis in POMS patients using PedsQL, reported mean HRQoL scores as 67.3-82.4 (15). The mean PedsQL score of our POMS patients was in the lower range of those reported in this meta-analysis.…”
Section: Discussionmentioning
confidence: 42%
“…Many organizations, e.g., the European Medicines Agency, emphasize the need to assess HRQOL in patients with chronic diseases. The effect of the disease on the quality of life (QoL) of children has been demonstrated in various chronic diseases such as cancer, rheumatic diseases, asthma, diabetes mellitus, neurological diseases including neurosurgical patients, fibromyalgia, demyelinating diseases, spinal muscular atrophy, cerebral palsy, or epilepsy (Ow et al, 2021).…”
Section: )mentioning
confidence: 99%
“…To support comprehensive evidence‐based recommendations for selecting the most suitable PROM for a given purpose, the Consensus‐based Standards for the selection of Health Measurement INstruments (COSMIN) initiative developed methodological standards for studies by selecting a minimum core set of outcomes that should be measured and reported in all clinical trials of a specific condition or trial population 16 . Systematic reviews are available for many neurologically‐based conditions: muscular dystrophy, 48,49 autism spectrum disorder, 50 child disability, 51 epilepsy, 42,52 survivors of brain tumour and other acquired brain injuries, 53 and pediatric multiple sclerosis 54 . The Core Outcome Measures in Effectiveness Trials are seeking consensus on what is important and meaningful to measure and are available for antiepileptic therapy in pediatric epilepsy 55 .…”
Section: Qol‐related Measures For Young People With Neurological Impa...mentioning
confidence: 99%
“…16 Systematic reviews are available for many neurologically-based conditions: muscular dystrophy, 48,49 autism spectrum disorder, 50 child disability, 51 epilepsy, 42,52 survivors of brain tumour and other acquired brain injuries, 53 and pediatric multiple sclerosis. 54 The Core Outcome Measures in Effectiveness Trials are seeking consensus on what is important and meaningful to measure and are available for antiepileptic therapy in pediatric epilepsy. 55 Core set outcome domains are available for tube-fed children with neurological impairments.…”
Section: Developing Core Outcome Sets For Health Measurementsmentioning
confidence: 99%